The outcome of septorhinoplasty surgery on olfactory function. (February 2016) - Randhawa, P.S.; Watson, N.; Lechner, M.; Ritchie, L.; Choudhury, N.; Andrews, P.J.
Abstract : Objectives: To assess olfactory outcomes in patients undergoing septorhinoplasty surgery in our unit. Design: Prospective cohort study. Setting: The Royal National Throat Nose and Ear Hospital, London. Participants: Forty‐three patients undergoing functional septorhinoplasty (Males = 26; mean age = 34.1 ± 12.2) were recruited into the study. Main outcome measures: The primary outcome of olfactory function was assessed using 'Sniffin sticks'. Our secondary outcomes were assessment of patient quality of life using the disease specific Sino‐nasal Outcome Test‐23 questionnaire (SNOT‐23) and a visual analogue scale for sense of smell. These measures were repeated at 12 weeks post operatively. Results: There was a significant change in the Sniffin' sticks score post‐operatively (8.3 versus 9.6; P  < 0.001). The SNOT‐23 score also showed a significant improvement post‐operatively (53.5 versus 40.4; P  < 0.001). A significant improvement was not found in the smell/taste question (question 21) of the SNOT‐23 questionnaire as well as the visual analogue scale for sense of smell. A difference in olfactory outcome was not found between open versus closed approaches, primary versus revision surgery and traumatic versus non traumatic cases. Conclusions: The results show a measured significant improvement in olfaction following functional Septorhinoplasty but not a subjective improvement in the patients perception of their sense of smell and hence not a clinically significant difference. The reasons for the measured improvement are not clear and are likely to be multifactorial.